In vitro and in vivo screening of commonly used acaricides against Ixodid ticks in South Omo pastoral areas, South-Western Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2025)
The study aimed to assess the in vitro and in vivo antitick efficacy of commonly used acaricides in order to suggest efficient acaricides to livestock owners was conducted in South Omo Zone, Southern Ethiopia. According to Drummond's method, the Adult Immersion Test (AIT) was applied to assess oviposition inhibition of engorged female ticks. Also, in vivo efficacy field trial of Deltamethrin 1% pour-on, Amitraz 12.5%, and Ivermectin 1% injection was conducted on a goat kept under a pastoral production system in the study area. A total of 528 fully engorged female R. decoloratus and R. pulchellus ticks were tested through the adult immersion test (AIT). A statistically significant (p